2015
DOI: 10.3109/07420528.2015.1082483
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin-induced ototoxicity and nephrotoxicity vary with circadian time of treatment and entail separate mechanisms

Abstract: The aminoglycoside antibiotic gentamicin can cause both ototoxicity and nephrotoxicity, the severity of which varies with circadian time of daily treatment. However, it is not yet resolved if such drug-induced adverse effects are independent or dependent phenomena. Two groups of 9 female Sprague-Dawley rats (200-250 g), each housed separately, entrained to a 12h light (06:00 to 18:00h)-12h dark cycle, received a daily subcutaneous injection of 100 mg/kg gentamicin. One group was treated at the beginning of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Chronotherapeutic strategies have proved beneficial in cancer treatment [ 98 ] where circadian-timed chemotherapy may improve outcomes. Optimising the timing of drugs with a narrow therapeutic index and significant circadian fluctuation, such as antibiotics, steroids and anticoagulants, could lead to significant clinical benefit from improvements in efficacy and minimisation of toxicity [ 97 , 99 ]. Benzodiazepines phase-shift the clock according to the time of day at which they are administered [ 100 ], and thus the circadian disruption effect could be minimised by administering the drug at the correct time of day relative to the patient’s circadian phase.…”
Section: Chronotherapeutics: Delivering the Right Treatment At The Rimentioning
confidence: 99%
“…Chronotherapeutic strategies have proved beneficial in cancer treatment [ 98 ] where circadian-timed chemotherapy may improve outcomes. Optimising the timing of drugs with a narrow therapeutic index and significant circadian fluctuation, such as antibiotics, steroids and anticoagulants, could lead to significant clinical benefit from improvements in efficacy and minimisation of toxicity [ 97 , 99 ]. Benzodiazepines phase-shift the clock according to the time of day at which they are administered [ 100 ], and thus the circadian disruption effect could be minimised by administering the drug at the correct time of day relative to the patient’s circadian phase.…”
Section: Chronotherapeutics: Delivering the Right Treatment At The Rimentioning
confidence: 99%
“…In accordance, higher nephrotoxicity and ototoxicity were demonstrated when it was dosed at the rest phase (ZT 2) in female rats, although clearance values were slightly higher at ZT 2 than ZT 14 (4.53 vs. 3.22 ml·min −1 ·kg −1 ; Blunston, Yonovitz, Woodahl, & Smolensky, 2015). Similarly, Oda et al evaluated the nephrotoxicity of cisplatin in mice and reported it as less toxic when clearance is higher, that is, active phase.…”
Section: Chronopharmacokinetics: Non‐clinical Datamentioning
confidence: 60%
“…Aminoglycoside antibiotics have been used for the treatment of gram-negative bacterial infection. However, these drugs have significant risks of nephrotoxicity and ototoxicity [21] . In the inner ear, systemic aminoglycosides cross the blood-labyrinth barrier (BLB) and can damage cochlear hair cells through several mechanisms such as apoptosis or release of reactive oxygen species (ROS), leading to permanent sensorineural hearing loss [22,23] .…”
Section: Discussionmentioning
confidence: 99%